Quality of Life in Iranian Patients with Oral and Head and Neck Cancer - Torabi, Molook (2021)
Objective: To assess sociodemographic factors and cancer information on patients' quality of life with head and neck cancer. Material and Methods: This cross-sectional study was conducted on 69 patients with head and neck cancer who attended in one of the oncology centers in Mashhad, Iran, from September 2019 to December 2019. Data was collected through a questionnaire consisted of demographic information (gender, age, educational level, and job) and cancer information (type, location, treatment, clinical stage) and standard quality of life questionnaire (QLQ-H&N35). Data analyzed in SPSS22 software using T, ANOVA, Linear regression tests at 0.05 significant levels. Results: 49 participants (72.1%) were men. The mean age was 60.48 ± 13.74 years. Forty-nine participants (72.1%) had squamous cell carcinoma and 26 participants (38.2%) had a larynx tumor. Forty-six participants (67.6%) were in clinical stage 3, mainly with a problem and complain about hard food swallowing, xerostomia and speech. The mean score of QLQ-H&N35 was 42.06 ± 20.12 from 90. Quality of life in 47.1% of cases was moderate. There was no significant relationship between gender, job, educational level, type and location of cancer (p>0.05). There was a significant relationship between the patient's age, clinical stage, type of treatment, and quality of life (p<0.05). Conclusion: Quality of life in 47.1% was moderate. Clinical stage, age of patients and type of treatment statically and significantly affected the quality of life. Assessing quality of life in HNC patients can identify important side effects of treatment that affected quality of life and look for ways to improve QoL.